Cue Valence Influences the Effects of Cue Uncertainty on ERP Responses to Emotional Events - Lin, Huiyan; Liang, Jiafeng; Liu, Ting; Liang, Ziping; Jin, Hua (Frontiers in Human Neuroscience, 2020)
Individuals often predict consequences, particularly emotional consequences, according to emotional or non-emotional signals conveyed by environmental cues (i.e., emotional and non-emotional cues, respectively). Some of these cues signify the consequences with certainty (i.e., certain cues), whereas others do not (i.e., uncertain cues). Several event-related potential (ERP) studies regarding non-emotional cues have suggested that the effects of cue uncertainty on attention to emotional events occur in both perception and evaluation processes. However, due to the limitations of previous studies, it is unclear what the effects of cue uncertainty would be in an emotional cue condition. Moreover, it is uncertain whether the effects of cue uncertainty are affected by cue valence (i.e., emotional and non-emotional cues). To address these questions, we asked participants to view cues and then to view emotional (positive or negative) pictures. The cues either did or did not indicate the emotional content of the picture. In the emotional cue condition, happy and fearful faces were used as certain cues indicating upcoming positive and negative pictures, respectively, and neutral faces were used as uncertain cues. In the non-emotional cue condition, scrambled faces outlined in red and blue indicated upcoming positive and negative pictures, respectively, and scrambled faces outlined in green served as uncertain cues. The results showed that for negative pictures, ERP responses in a time range between 60 and 1000 ms were shifted to a more negative direction in the certain condition than in the uncertain condition when the cues were emotional. However, the effect was the reverse for positive pictures. This effect of cue uncertainty was similar in the non-emotional cue – negative condition. In contrast, there was no effect of cue uncertainty in the non-emotional cue – positive condition. Therefore, the findings indicate that cue uncertainty modulates attention toward emotional events when the events are signified by emotional cues. The findings may also suggest that cue valence modulates the effects of cue uncertainty on attention to emotional events.